2022
DOI: 10.7150/ijms.64763
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry polyphenol extracts attenuated senescence through inhibition of Ras/ERK via promoting Ras degradation in VSMC

Abstract: Ageing is one of the major risk factors of human diseases, including cancer, diabetes, and cardiovascular disease. Mulberry exhibits a wide range of functions, such as anti-oxidant, anti-inflammation, and anti-diabetes. In this study, we investigated the role of mulberry polyphenol extract (MPE) in K-Ras-induced senescence of smooth muscle cells. Forced expression of K-Ras enhanced senescence of smooth muscle A7r5 cells as shown by the elevation of β-galactosidase activity. Treatment with MPE significantly rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Treatment with MPE reversed the K-Ras-induced phenomenon. In contrast, MPE mitigates K-Ras-induced senescence and promoted proliferation of smooth muscle cells through the downregulation of K-Ras expression and its downstream signals 17 . The difference findings between this study and previous report 17 may result from distinct Ras expression pattern.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Treatment with MPE reversed the K-Ras-induced phenomenon. In contrast, MPE mitigates K-Ras-induced senescence and promoted proliferation of smooth muscle cells through the downregulation of K-Ras expression and its downstream signals 17 . The difference findings between this study and previous report 17 may result from distinct Ras expression pattern.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, MPE mitigates K-Ras-induced senescence and promoted proliferation of smooth muscle cells through the downregulation of K-Ras expression and its downstream signals 17 . The difference findings between this study and previous report 17 may result from distinct Ras expression pattern. Minamino et al demonstrated that transient overexpression of Ras stimulated proliferation of smooth muscle cells whereas senescence was observed after post-transfection for 72 h 27 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Pan et al (2019) found that resveratrol, as a natural stilbene with antiobesity effects, can enhance the expression of thermogenic-related proteins UCP1 and PRDM16 by activating SIRT1/PGC-1α (Pan et al, 2019). Mulberry leaves have been proven to have a variety of biological activities, such as antidiabetic and anti-inflammatory effects (Chen et al, 2022). Cheng et al (2022) showed that mulberry may induce the browning of iWAT by increasing the expression of brown marker genes and beige-specific genes (such as PRDM16) (Cheng et al, 2022).…”
Section: Prdm16 May Serve As a Potential Therapeutic Target In Obesit...mentioning
confidence: 99%
“…Mulberry (Morus alba) has traditionally been used to treat a wide range of conditions, including hypertension, diabetes, anemia, and malaria (Lallo, et al, 2020). Numerous studies have demonstrated the anticancer properties of mulberry extract, which can suppress the growth of breast cancer (Chen, et al, 2022;Wani, et al, 2023). Morus alba extract is reported to contain several active compounds including morusin (Panek-Krzyśko and Stompor-Gorący, 2021).…”
Section: Introductionmentioning
confidence: 99%